2012
DOI: 10.1097/iae.0b013e318227aa09
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Visual Outcome After Intravitreal Anti-Vegf Injection for Naive Myopic Choroidal Neovascularization

Abstract: Purpose: The aim of this study was to evaluate the prognostic factors of visual outcome after intravitreal anti-vascular endothelial growth factor injection in patients with myopic choroidal neovascularization (CNV).Methods: Forty eyes of 40 consecutive patients with myopic CNV who had received intravitreal ranibizumab or bevacizumab injections were retrospectively reviewed. Baseline visual acuity, presence of lacquer crack, dark rim, peripapillary choroidal atrophy size, and location of myopic CNV were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 30 publications
3
22
0
Order By: Relevance
“…Our results showed that among the pretreatment factors analysed, baseline BCVA was the main variable influencing the BCVA 2 and 3 years after treatment. Therefore, patients with a higher BCVA at baseline had a better BCVA after treatment, as described by other authors [22,31]. This fact may be associated with minor initial damage to the photoreceptors in these patients.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Our results showed that among the pretreatment factors analysed, baseline BCVA was the main variable influencing the BCVA 2 and 3 years after treatment. Therefore, patients with a higher BCVA at baseline had a better BCVA after treatment, as described by other authors [22,31]. This fact may be associated with minor initial damage to the photoreceptors in these patients.…”
Section: Discussionsupporting
confidence: 57%
“…Age was another factor independently correlated with BCVA outcome at 3 years, a finding consistent with results of a prospective study by Gharbiya et al [24], in which the authors reported that for each 1-year increase in baseline patient age there was a mean decrease in final BCVA of 0.39 letters. However, the effect of age on the visual prognosis of mCNV eyes treated with anti-VEGF agents has not been as well described as its influence on mCNV eyes treated with PDT [22,31]. A possible explanation is that PDT may provoke some damage to the retina or retinal pigment epithelium, and that the ability to recover from such damage can be affected by a patient's age.…”
Section: Discussionmentioning
confidence: 99%
“…14,27 Previous studies that have evaluated the use of anti-VEGF therapy in myopic CNV were also rather heterogeneous, as the studies have included prior treated eyes as well as non-subfoveal CNV. [28][29][30] In order to further assess the long-term efficacy of anti-VEGF therapy for myopic CNV, we evaluated the 2-year outcomes in the use of intravitreal bevacizumab and ranibizumab as the primary treatment for subfoveal myopic CNV. We also evaluated the prognostic factors that might influence the visual outcomes following anti-VEGF therapy for myopic CNV.…”
Section: Introductionmentioning
confidence: 99%
“…6,[8][9][10][11][12] The mean final VA in patients treated with anti-VEGF drugs reported in the literature ranges from 0.23 to 0.55 (Table 2). [6][7][8][9][10][11][12][31][32][33][34][35][36] More importantly, in studies which have compared anti-VEGF with PDT treatment for myopic CNV, patients treated with anti-VEGF generally achieved better visual outcomes compared with the group treated with PDT. 7,24,25 It is important to note, however, that in these studies, patients…”
Section: Discussionmentioning
confidence: 99%